Spine Trauma Secondary to Diving Accidents: A Seven-year Retrospective Study in Puerto Rico - Carballo-Cuello, César M.; De Jesus, Orlando; Fernández-de Thomas, Ricardo J.; de Jesús-Espinosa, Aixa; Vigo-Prieto, Juan A. (Puerto Rico Health Sciences Journal, 2022)
Objective: Review the profile of patients with spinal trauma after diving accidents referred to the Puerto Rico Medical Center. This study intended to develop more awareness of the risks of spinal cord injury after diving. Methods: The patient’s records for diving accident cases referred to our center during January 2014 until December 2020 were assessed retrospectively. The cases were evaluated according to sex, age, vertebral level, and neurological deficit. The Puerto Rico Medical Center is the only level 1 trauma center in Puerto Rico; therefore, this study likely included all the cases of diving injury on the island. Results: Sixty five patients with a median age of 29 years were identified consisting primarily of males (94%). The regions affected included the cervical (96%), thoracic (2%), and lumbar (2%) spine. Twenty-seven patients (42%) developed a spinal cord injury secondary to a diving accident. Involvement of the C4, C5, or C6 vertebral level, was significant for the development of a spinal cord injury. Diving accidents occurring at beaches were the most common cause. Conclusion: In Puerto Rico, there is a yearly incidence of 9.3 diving accidents causing spinal trauma; these accidents most frequently affect the C6 vertebra. These diving accidents mainly occur in young individuals, predominantly at beaches. Most of our patients were neurologically intact after their diving accident, although 42% sustained a spinal cord injury. This study provided a better understanding of this traumatic event and determined its most affected levels, accident sites, and population involved.